Study of Mechanical and Thermal Behavior for Epoxy Reinforced by Fibers - K. Hameed, Hayat (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this study, epoxy was used as a matrix for composite materials, with E-glass fiber, jute and PVC fiber which was woven roving fiber, as reinforcement with volume fraction (Vf= 30%). There are two of prepared types of epoxy non reinforced, epoxy reinforced with E-glass, jute and PVC fibers including study of mechanical tests (Impact test, Bending test) different temperature and thermal conductivity and calculating the temperatures coefficient at different temperature. Results show that elastic modulus at rate values decrease to the increase of temperature and the impact strength, impact energy and thermal conductivity increase with increase temperature.